Why Status Matters for Inequality - Ridgeway, Cecilia L. (American Sociological Review, 2014)
To understand the mechanisms behind social inequality, this address argues that we need to more thoroughly incorporate the effects of status—inequality based on differences in esteem and respect—alongside those based on resources and power. As a micro motive for behavior, status is as significant as money and power. At a macro level, status stabilizes resource and power inequality by transforming it into cultural status beliefs about group differences regarding who is “better” (esteemed and competent). But cultural status beliefs about which groups are “better” constitute group differences as independent dimensions of inequality that generate material advantages due to group membership itself. Acting through micro-level social relations in workplaces, schools, and elsewhere, status beliefs bias evaluations of competence and suitability for authority, bias associational preferences, and evoke resistance to status challenges from low-status group members. These effects accumulate to direct members of higher status groups toward positions of resources and power while holding back lower status group members. Through these processes, status writes group differences such as gender, race, and class-based life style into organizational structures of resources and power, creating durable inequality. Status is thus a central mechanism behind durable patterns of inequality based on social differences.